PEMIDANAAN TERHADAP ANAK YANG BERKONFLIK DENGAN HUKUM DITINJAU DARI HUKUM POSITIF DI INDONESIA - Kadek Dwi Marta Prandika; Putu Eka Trisna Dewi; Karyoto (Jurnal Hukum Saraswati, 2025)
The development of juvenile delinquency and criminal acts which is very significant at this time is influenced by several factors including, socio-economic factors, family factors (broken homes), social factors, environmental factors and rapid technological developments. Apart from the factors listed above, the most basic things are that children easily commit juvenile delinquency, where in current conditions children are rarely given an understanding regarding the consequences that will arise. Apart from that, the influencing factors are related to mitigating policies and the role of the government and existing officials who are still hesitant in making a decision. Actions carried out by children do not necessarily come from within the child, this also arises from environmental and social factors so that crimes will easily occur among children. From the actions taken there will also arise sanctions or a criminal process which will have a deterrent effect on children. This research uses a normative juridical method, by analyzing primary legal materials, secondary legal materials and tertiary legal materials using normative and qualitative juridical analysis, then arranged systematically. The types of legal materials that will be used are in accordance with the purpose of discussing this material, namely: Primary legal materials consisting of: Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.